Characteristics of the Psychologists’ Role Profiles - Khomulenko, Borus (Psychological Prospects Journal, 2015)
The article presents the research results of psychologist’s personality role structure. It describes the features of personality with different role profiles of psychologist. The article represents the characteristics of typological profiles «Coach-Teacher», «Consultant-Psychotherapist», «Consultant-Teacher», «Scientist-Teacher», which were obtained by the cluster analysis. The profiles are characterized by the role competence, reflexivity and emotional intelligence. It is shown that the role depth as the ability to «get used» and feel professional is inherent to psychologists of the type «Scientist-Teacher». It is proved that psychologists who are more engaged in scientific and pedagogical activity, are less able to manage their emotions, and are characterized by emotional rigidity. The study shows, that the ability to spontaneous emotional response, emotional states stimulating, emotional self-motivation is less appropriate to psychologists engaged in psychotherapy, psychocorrectional and consulting work. The present empirical study determines that psychologists included in research and teaching activities possess less empathy as a characteric feature of emotional intelligence. It is shown that the research and teaching activities of psychologists such as «Scientific-Teacher» are characterized by the ability to recognize emotional states of others. It is proved that reflexivity is professionally important characteristic of such types of psychologists as «Coach-Teacher», «Consultant-Teacher». The generalization of empirical research suggests that typological analysis of psychologist personality role structure can give features of his professionally important psychological qualities.